The C-Terminal End of HIV-1 Vpu Has a Clade-Specific Determinant That Antagonizes BST-2 and Facilitates Virion Release - Sharma, Shilpi (J Virol, 2019)
The cellular protein bone marrow stromal antigen-2 (BST-2)/tetherin acts against a variety of enveloped viruses by restricting their release from the plasma membrane. The HIV-1 accessory protein Vpu counteracts BST-2 by downregulating it from the cell surface and displacing it from virion assembly sites. Previous comparisons of Vpus from transmitted/founder viruses and between viruses isolated during acute and chronic infection led to the identification of a tryptophan at position 76 in Vpu (W76) as a key determinant for the displacement of BST-2 from virion assembly sites. Although present in Vpus from clades B, D, and G, W76 is absent from Vpus from clades A, C, and H. Mutagenesis of the C-terminal region of Vpu from two clade C viruses led to the identification of a conserved LL sequence that is functionally analogous to W76 of clade B. Alanine substitution of these leucines partially impaired virion release. This impairment was even greater when the mutations were combined with mutations of the Vpu β-TrCP binding site, resulting in Vpu proteins that induced high surface levels of BST-2 and reduced the efficiency of virion release to less than that of virus lacking vpu. Microscopy confirmed that these C-terminal leucines in clade C Vpu, like W76 in clade B, contribute to virion release by supporting the displacement of BST-2 from virion assembly sites. These results suggest that although encoded differently, the ability of Vpu to displace BST-2 from sites of virion assembly on the plasma membrane is evolutionarily conserved among clade B and C HIV-1 isolates. IMPORTANCE Although targeted by a variety of restriction mechanisms, HIV-1 establishes chronic infection in most cases, in part due to the counteraction of these host defenses by viral accessory proteins. Using conserved motifs, the accessory proteins exploit the cellular machinery to degrade or mistraffic host restriction factors, thereby counteracting them. The Vpu protein counteracts the virion-tethering factor BST-2 in part by displacing it from virion assembly sites along the plasma membrane, but a previously identified determinant of that activity is clade specific at the level of protein sequence and not found in the clade C viruses that dominate the pandemic. Here, we show that clade C Vpu provides this activity via a leucine-containing sequence rather than the tryptophan-containing sequence found in clade B Vpu. This difference seems likely to reflect the different evolutionary paths taken by clade B and clade C HIV-1 in human populations.